Influence of Wet or Dry Conditions on the Fatigue Life of Grout Cementitious Materials under Cyclic Loading - Ruirong Zhou; Xiaochuan Qin; Jianfang Sha; Fei Guo; Wu Qi (Geofluids)
Grouting cementing material is a kind of sealing cementing material widely used in underground space. However, the influence of the fatigue life after cementation hardening is often ignored when subjected to, for example, cyclic traffic loads. Therefore, it also often causes engineering problems such as joint cracking, leakage, and plate bottom emptiness. The prediction of fatigue life of grouting cementation material is of great significance to the stability of underground tunnel structure. In this paper, the fatigue characteristics of hardened grout specimens under different fatigue loads and cycle frequencies are studied. Test the cyclic compression load repeatedly in different environments (dry or wet). The results show that the fatigue properties of grout materials are reduced in both air and water and significantly reduced when the stress level is 65% or above of static compressive strength in wet environment, especially when the loading frequency in water drops from 10 to 35 Hz. The main mechanism of fatigue life decline is splitting effect caused by water extrusion in the sample under cyclic loading. Water washes away abrasive action in the cracks. The dry-wet fatigue aging characteristics of superhigh strength grout cement materials lay a foundation for the evolution simulation of underground foundation structures under cyclic loading.